Microfluidics for Biosensing and Diagnostics - Inglis, David W.; Warkiani, Majid Ebrahimi; Qasaimeh, Mohammad A.; Chen, Weiqiang (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Efforts to miniaturize sensing and diagnostic devices and to integrate multiple functions into one device have caused massive growth in the field of microfluidics and this integration is now recognized as an important feature of most new diagnostic approaches. These approaches have and continue to change the field of biosensing and diagnostics. In this Special Issue, we present a small collection of works describing microfluidics with applications in biosensing and diagnostics.